Psychological Portrait of Alice: Ego Defenses in Lewis Carroll’s “Through the Looking Glass” - Pramesti, Shavana Edelia; Rahayu, Endang Yuliani (University of Surakarta, 2025)
The purpose of this research is to analyze the ego defence mechanisms of the main character in “Alice Through the Looking Glass”. This research identifies specific . n response to the challenges she faces in the fantastical world. Employing a text-oriented context methodology to analyze her psychological behaviour throughout the narrative. These mechanisms are crucial for understanding Alice’s character development, as they reveal her struggles with identity, self-perception, and the pressures of her environment. The findings indicate that Alice’s use of ego defense mechanism serves as a coping strategy, allowing her to navigate the complexities of her experiences. The motivation behind her reliance on these defenses is explored, highlighting her desire to protect herself from emotional pain and uncertainty. By analyzing Alice’s character through the lens of ego defense mechanisms, this research provides valuable insight into her psychological landscape and the broader themes of identity and resilience in the film. The study underscores the significance of understanding psychological mechanisms in character development, offering a nuanced perspective on Alice’s journey and the intricate dynamics within the narrative.